DEMERSAL FISHERIES OF VIZHINJAM - Radhakrishnan, N (Indian Journal of Fisheries, 2011)
The averag(5 annual yield from the demersal fisheries of Vizhinjam amountsto 773 tomtes which forms about 29% of the total marine fish production of theplace. The seasonality and the size composition of the fishery for silver bellies,balistids, pomfrets, prawns, cat fishes, scienids, elasmobranchs and perches aregiven. An analysis of the catch per unit of effort by the different gears showsthat the general decline from 1965 to 1967 is probably due to reduction in theavailability